Effect of a contraceptive pill containing estradiol valerate and dienogest (E2V/DNG) in women with menstrually-related migraine (MRM) - Nappi, Rossella E.; Terreno, Erica; Sances, Grazia; Martini, Ellis; Tonani, Silvia; Santamaria, Valentina; Tassorelli, Cristina; Spinillo, Arsenio (Contraception (Stoneham), 2013)
Combined hormonal contraception might worsen migraine in sensitive women, especially during the free-hormone interval, and raise concerns about the vascular risk. The characteristics of a contraceptive pill containing estradiol valerate/dienogest (E2V/DNG) might be of potential benefit in women with menstrually related migraine (MRM) who choose to use oral contraception for birth control. This was a prospective diary-based pilot study. Thirty-two women (age >35 years) [n=18 who had never used combined oral contraceptives (COCs) and n=14 who had previously used COCs] diagnosed with MRMs according to the International Headache Society criteria were included. During the observational period, women filled in a diary with the clinical characteristics of migraine attacks. After a three-cycle run-in period, each subject received a COC containing E2V/DNG (Qlaira®/Natazia®; Bayer HealthCare, Berlin, Germany) administered using an estrogen step-down and progestogen step-up approach. Follow-up evaluations were scheduled at the last cycle of run-in and at the third and sixth cycles of treatment. The number of migraine attacks was significantly reduced at the third (p<.001) and sixth cycles (p<.001) in comparison with the run-in period. A similar result was evident for the duration (p<.001 at the third and p<.001 at the sixth cycle) as well as for the severity of head pain (p<.001 at the third and p<.001 at the sixth month). Indeed, a significantly lower number of analgesics were used at the third cycle (p<.001) in comparison with baseline, and a further decrease was evident at the sixth cycle (p<.001) in comparison with the third cycle of E2V/DNG use. Interestingly, duration and severity of head pain were significantly correlated with the number of days of dysmenorrhea at the third cycle (r=.89, p=.000 and r=.67, p=.02; respectively) and at the sixth cycle (r=.76, p=.000 and r=.62, p=.04; respectively) in women without complete remission of menstrual cramps during the study period. The present diary-based pilot study indicates that the use of a pill containing EV2/DNG for six cycles has a positive effect in women with MRM and suggests an association between dysmenorrhea with COCs use as a potential feature of refractory head pain.